The low-income countries of the Commonwealth of Independent States : progress and challenges in transition - Shiells, Clinton R.; Sattar, Sarosh (Washington, D.C. : International Monetary Fund : World Bank, 2004)
This volume is the record of the Lucerne conference. The first chapter provides a summary of the major findings and key themes emerging from the conference.
Summary of and selected papers from the Low-Income Countries of the CIS: Progress and Challenges conference, held January 20-22, 2003, in Lucerne, Switzerland.
Includes bibliographical references.
osc 30/8/16
Loans
Keywords: Economic conditions; Poverty; Expenditures, Public; Commerce; Former Soviet republics